Thermal Degradation of Polystyrene - De, Somer P. (My University, 1973)
In this study uninhibited styrene, degassed under high vacuum (10ˉ⁶ mm Hg), was thermally polymerized in bulk of 10ˉ⁶ mm Hg to almost complete conversion. The samples so obtained were thermally degraded under the same high vacuum conditions at temperatures ranging between 270°C and 340°C for different time intervals over the whole range of degradation. The breakdown of the polymer, through changes in number, weight average molecular weights, polydispersity and molecular weight distribution, was investigated using gel permeation chromatography. A mechanism of degradation was sought, and the breakdown explained by a combined process of deploymerization and chain scission. Scission constants were determined and compared with the constants, obtained from a polystyrene having much larger molecular weights.
Keywords: Chemical Engineering; Chemical Engineering